Reducing Academic Stress through Autonomy Fulfillment: A Self Determination Theory Solution in the Context of Students' Cognitive Load - Labibah Sayaka Ilma; Abdul Muhid; Arif Ainur Rofiq (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Academic stress has emerged as a critical issue in contemporary education, with increasing learning demands and structural pressures contributing to students’ psychological strain. Specific Background Cognitive Load Theory explains that excessive academic demands, arising from material complexity, task accumulation, and inefficient instructional design, exceed students’ working memory capacity and intensify stress, while educational policies and curriculum structures at the exosystem level further reinforce this burden. Knowledge Gap Existing studies predominantly examine academic stress through isolated internal or external factors, with limited integration of cognitive load, exosystem structures, and autonomy within a unified analytical framework. Aims This study aims to explain the role of cognitive load in the emergence of academic stress, analyze exosystem factors that exacerbate learning burden, and evaluate autonomy fulfillment within Self-Determination Theory as a strategy for reducing academic pressure. Results The findings indicate that excessive cognitive load significantly contributes to academic stress, while dense curricula, rigid schedules, and assessment policies intensify this condition; autonomy-supportive learning environments reduce extraneous cognitive load and strengthen students’ self-regulation in managing academic demands. Novelty This study integrates Cognitive Load Theory, Bronfenbrenner’s ecological perspective, and Self-Determination Theory to provide a comprehensive explanation of academic stress. Implications The findings highlight the necessity of flexible curriculum design, autonomy-supportive instructional practices, and policy reform to promote students’ mental well-being and sustainable learning environments. Highlights: Excessive learning demands and structural academic arrangements are closely associated with heightened psychological strain. Policy-level curriculum density and assessment practices contribute to sustained mental burden among learners. Learner choice and self-regulation function as protective mechanisms against accumulated academic pressure. Keywords: Academic Stres, Autonomy, Self Determination, Cognitive Load.